Exploration of the Application of Computer Science and Technology in the Context of Big Data - Wang, Zijun (Journal of Theory and Practice of Management Science, 2025)
Since the emergence of computer science and technology, there has been a fundamental change in the way people manage and analyze data, which has driven the informatization and digital transformation of human society.Big data is a product of highly developed information technology, and computer science and technology are the necessary foundation for realizing the value and development of big data.At present, in the process of developing big data resources, the application of computer science and technology still faces some difficulties. Therefore, practitioners in related fields need to strengthen the development and innovation of technology, so as to promote the development and progress of human society.